Development of an Information System for Student Data Management at Mts.S Krueng Seumideun, Pidie Regency - Abubakar (Journal Dekstop Application (JDA), 2023)
The implementation of a Student Information System at Mts. S Krueng Seumideun in Pidie Regency aims to improve the efficiency and accuracy of managing student data. Previously, the school relied on manual methods using Microsoft Word and Excel for data entry and report generation, which were slow and error-prone. This research focuses on designing, developing, and implementing a computerized system using Microsoft Visual Basic 6.0 and Microsoft Access 2007. The development process included several phases: feasibility study, system planning, system analysis, and implementation. The system features a Student Data Input Form that captures essential student information such as registration number, student ID, name, and academic details, streamlining data entry. A Main Menu was created to provide access to various administrative functions, including report generation and data retrieval. The system’s implementation involved coding, testing, and training staff to ensure smooth adoption. Performance testing showed that the new system was faster and more accurate than the previous manual methods. By automating administrative tasks, the system reduces human error, speeds up data processing, and allows for quicker, data-driven decision-making. The shift to a digital platform will enhance administrative efficiency, support better resource management, and improve the overall educational environment.